Extraskeletal Ewing’s Sarcoma Arising from the Sciatic Nerve: A Diagnostic Challenge - Aadhar Sharma; Kate Brown; John Skinner; Jeremy Whelan; Michael Fox (Case Reports in Surgery)
Ewing’s sarcoma is a common bone tumour of childhood but is a rare occurrence in individuals over 20 years of age. Few cases are reported as originating from peripheral nerves. We present an unusual case of extraosseous Ewing’s sarcoma originating from the sciatic nerve in a 66-year-old patient which had the clinical hallmarks of a benign nerve sheath tumour. Following discussion at a multidisciplinary meeting, excision biopsy of the suspected benign nerve sheath tumour was planned. At operation, the mass had malignant features. Histology confirmed the presence of Ewing’s sarcoma. Due to the morbidity of nerve resection, radiotherapy and chemotherapy were commenced. Ewing’s sarcoma is known to mimic benign pathologies. In this case there were subtle signs of a malignant process in the form of unremitting pain. It is vital to keep in mind the less common tumours that can affect the peripheral nervous system in such cases.